Money Laundering: A Three Step Secrete Game - Arman Md; Ikhsan Nendi (Al-Makki Publisher, 2023)
This paper describes, theoretically, what money laundering is and how it is done following some partnered activities over time. This paper also looks for electronic money laundering and found some related and predefined functions which are completed using electronic gadgets and the Internet. To give a clear view on money laundering, the author thinks that it is necessary to make it clear first about the characteristics of money laundering, the reasons behind it, and how it creates negative impacts on the business and economy of a country. In most nations, money laundering is a crime and economically developed countries built strong fortress against money launderers but laundering is not stopped. So, this paper tries to find out what the launderers do and find innovative (legally unaccepted) ways to make their illicit money legal.